Pemanfaatan Lahan Pekarangan Rumah Tangga Wanita Tani untuk Tanaman Obat Keluarga (Toga) di Kecamatan Bagelen, Kabupaten Purworejo - Istiko Agus Wicaksono; Didik Widiyantono; Arta Kusumaningrum (Jurnal Riset Agribisnis dan Peternakan, 2018)
This research was conducted in Bagelen Subdistrict, Purworejo Regency with a research focus "Utilization of Farm Women Yard Home for Family Medicinal Plants (TOGA) in Bagelen District, Purworejo Regency". Whereas a woman farmer in Bagelen District, Purworejo Regency realizes that using her yard for Toga plants has enormous benefits. In addition to earning income from the Toga plant, female farmers can also use the Toga plant for healthy crops. The objectives of this study are 3, namely: 1) Knowing the benefits of yard land for TOGA plants in Bagelen District, Purworejo Regency, 2) Knowing the acceptance of TOGA plants in Bagelen District, Purworejo Regency, and (3) Knowing the marketing channels of TOGA plants in Bagelen District This research was conducted on 30 female farmer respondents in Bagelen District, Purworejo Regency. The research was conducted using descriptive analysis. The results of this study are 1) The average female farmer in Bagelen District, Purworejo Regency uses her yard for Toga plants with a variety of land areas that she cultivates, 2) Acceptance of female farmers obtained from the use of yard land for Toga plants is the lowest yield of IDR 9,000. 00 while the highest yield is Rp. 12,000,000.00, and 3) The marketing channels carried out by female farmers in Bagelen District, Purworejo Regency are direct selling or selling directly to consumers who are usually taken directly to the market in the market. villages and districts.